2017
DOI: 10.11609/jott.3445.9.11.10961-10963
|View full text |Cite
|
Sign up to set email alerts
|

<b>The Vulnerable Indian Skimmer <I>Rynchops albicollis</I> Swainson, 1838 (Aves: Charadriiformes: Laridae) breeding in Odisha, eastern India</b>

Abstract: The Indian Skimmer is a globally threatened bird native to Bangladesh, India, Myanmar, Nepal, Pakistan, and Vietnam.  In India, it is more confined to the north, from Punjab through Uttar Pradesh, Madhya Pradesh to West Bengal, extending up to Odisha.  Earlier, the bird was known to breed only in Uttar Pradesh and Madhya Pradesh, we confirm here the breeding of the Indian Skimmer along the river Mahanadi near Mundali, Odisha, eastern India.  So, further monitoring at the breeding site and survey along the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Many species of birds are known to utilize the river and its associated habitats to complete partial or entire lifecycles (Page & Gill 1994;Vaughan et al 2007;Froneman et al 2011;Rahmani 2012). Additionally, the riverine system has an intricate relationship with humans, which sometimes causes overexploitation and habitat degradation, and can adversely impact the populations of species like the Indian Skimmer and the Black-bellied Tern Sterna acuticauda (Kar et al 2018;. In our study area, we observed multiple pressures on the river system, which negatively impacts the breeding cycle of Indian Skimmer and may severely affect the species at the population level on a long run.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Many species of birds are known to utilize the river and its associated habitats to complete partial or entire lifecycles (Page & Gill 1994;Vaughan et al 2007;Froneman et al 2011;Rahmani 2012). Additionally, the riverine system has an intricate relationship with humans, which sometimes causes overexploitation and habitat degradation, and can adversely impact the populations of species like the Indian Skimmer and the Black-bellied Tern Sterna acuticauda (Kar et al 2018;. In our study area, we observed multiple pressures on the river system, which negatively impacts the breeding cycle of Indian Skimmer and may severely affect the species at the population level on a long run.…”
Section: Discussionmentioning
confidence: 79%
“…It gradually helps in identifying key conservation priorities and monitoring the effect of change in policy and environment (Havstad & Herrick 2003;Giron-Nava et al 2017). However, long-term ecological monitoring of the waterbirds and their associated habitats is limited in India (Prasad et al 2002;Kar et al 2018;Singh & Sharma 2018;Debata et al 2019). The riverine systems of India facilitate the occurrence of river-dependent birds by providing shelter, forage, and breeding grounds (Islam & Rahmani 2008;Rajguru 2017;Sinha et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a consequence of habitat fragmentation and degradation of lowland river and lake systems throughout much of their range (BirdLife International 2020). At present, India is the last remaining breeding ground for Indian Skimmers where they mainly breed in Ganges (Ankit et al 2018;Mital et al 2019), Chambal (Das 2015), Son (Dilwar and Sharma 2016) and Mahanadi rivers (Debata et al 2017). Bangladesh is the last remaining stronghold for nonbreeding Indian Skimmers in winter, and >1,000 skimmers can still be seen in Nijhum Dweep National Park in the south-central coast of the country annually (Islam and Khan 2005;Das 2015;Das et al 2020a).…”
mentioning
confidence: 99%
“…Yet, Mohsanin (2014) reported a 90 % decrease of Indian skimmers in Bangladesh between 2000 and 2013, and the species is now considered Critically Endangered by IUCN Bangladesh (2015). Any form of protection or management, however, is hindered by specific ecological knowledge (Rahmani 2012;Debata et al 2017;Das et al 2020a).…”
mentioning
confidence: 99%